Evaluation of an institutional project to improve venous thromboembolism prevention. (December 2016) - Minami, Christina A.; Yang, Anthony D.; Ju, Mila; Culver, Eckford; Seifert, Kathryn; Kreutzer, Lindsey; Halverson, Terri; O'Leary, Kevin J.; Bilimoria, Karl Y.
Abstract : BACKGROUND: Northwestern Memorial Hospital (NMH) was historically a poor performer on the venous thromboembolism (VTE) outcome measure. As this measure has been shown to be flawed by surveillance bias, NMH embraced process‐of‐care measures to ensure appropriate VTE prophylaxis to assess healthcare‐associated VTE prevention efforts. OBJECTIVE: To evaluate the impact of an institution‐wide project aimed at improving hospital performance on VTE prophylaxis measures. DESIGN: A retrospective observational study. SETTING: NMH, an 885‐bed academic medical center in Chicago, Illinois PATIENTS: Inpatients admitted to NMH from January 1, 2013 to May 1, 2013 and from October 1, 2014 to April 1, 2015 were eligible for evaluation. INTERVENTION: Using the define‐measure‐analyze‐improve‐control (DMAIC) process‐improvement methodology, a multidisciplinary team implemented and iteratively improved 15 data‐driven interventions in 4 broad areas: (1) electronic medical record (EMR) alerts, (2) education initiatives, (3) new EMR order sets, and (4) other EMR changes. MEASUREMENTS: The Joint Commission's 6 core measures and the Surgical Care Improvement Project (SCIP) SCIP‐VTE‐2 measure. RESULTS: Based on 3103 observations (1679 from January 1, 2013 to May 1, 2013, and 1424 from October 1, 2014 to April 1, 2015), performance on the core measures improved. Performance on measure 1 (chemoprophylaxis) improved from 82.5% to 90.2% on medicine services, and from 94.4% to 97.6% on surgical services. The largest improvements were seen in measure 4 (platelet monitoring), with a performance increase from 76.7% adherence to 100%, and measure 5 (warfarin discharge instructions), with a performance increase from 27.4% to 88.8%. CONCLUSION: A systematic hospital‐wide DMAIC project improved VTE prophylaxis measure performance. Sustained performance has been observed, and novel control mechanisms for continued performance surveillance have been embedded in the hospital system. Journal of Hospital Medicine 2016;11:S29–S37. © 2016 Society of Hospital Medicine